Comparison of Travel Time Reliability of Different Bus Service Providers: A Case Study of Airport to Narayan Gopal Chowk Route, Kathmandu - Kumar Thapa, Santosh; Pradhananga, Rojee; Shrestha, Saurav (International Journal on Engineering Technology, 2024)
The diminishing preference for the public transportation system in the Kathmandu Valley has been a longstanding issue, attributed to factors such as uncontrolled urbanization, increased motorization, inadequate transit infrastructure, and diminished reliability. The issue of less reliability of public transport in Kathmandu has drawn significant interest of public authorities, policy makers, planners and researchers. The lack of reliability in the public transportation system may compel commuters to choose personal vehicles, primarily motorcycles and cars. The increase in these smaller vehicles, sharing routes with larger ones, not only leads to an increase in congestion but also diminishes overall reliability. Hence, it becomes imperative to maintain the public transport system at an optimal level of reliability. Thus, this research focuses on the performance of public transport, particularly buses, employing measures of travel time reliability. Planning time and planning time index are used as a measure of the travel time reliability. This study includes a comparative analysis of the travel time reliability among different bus service providers operating on the case study route. On board technique was adopted to collect the data. Among the different public service providers operating in the area, four bus service providers Mahanagar Yatayat, Mahasagar Yatayat, Mayur Yatayat and Khwopa Yatayat were selected for this study. The comparison of travel time reliability among various bus service providers was conducted using an Analysis of Variance (ANOVA) test and post-hoc test.